Sensory Processing and Attention Profiles Among Children With Sensory Processing Disorders and Autism Spectrum Disorders - Crasta, Jewel E.; Salzinger, Emily; Lin, Mei-Heng; Gavin, William J.; Davies, Patricia L. (Frontiers in Integrative Neuroscience, 2020)
This study explores the differences in the profile of relationships between sensory processing and attention abilities among children with sensory processing disorders (SPD), autism spectrum disorders (ASD) and typically-developing (TD) children. The Test of Everyday Attention for Children (TEA-Ch), a performance-based measure of attention was administered to 69 children (TD: n=24; SPD: n=21; ASD: n=24), ages 6-10 years. All participants’ parents completed the Short Sensory Profile (SSP), a standardized parent-report measure of sensory-related behaviors. Discriminant analyses using the TEA-Ch and the SSP domains revealed two classification functions; the first revealed that both clinical groups significantly differed from the TD group with greater sensory processing challenges in the categories of auditory filtering, under-responsive-seeks sensation, low-energy-weak and taste smell sensitivity subscales of the SSP. The second function discriminated between the two clinical groups, indicating that children with ASD had significantly greater control and sustained attention deficits and less sensory issues than children with SPD. Together, the two functions correctly classified 76.8% of the participants as to their group membership. The different profiles of sensory processing and attention abilities in children with SPD and ASD may provide guidance in identifying appropriate individualized therapeutic strategies for these children.